EXPLORING PROFITABILITY PONTENTIALS IN GROUNDNUT (ARACHIS HYPOGAEA) PRODUCTION THROUGH AGROFORESTRY PRACTICES: A CASE STUDY IN NIGERIA - I. B. Adinya; E. E. Enun; J. U. Ijoma (Journal of Animal and Plant Sciences, 2010)
This study was carried out to determine costs –returns profitability in groundnut –based alley cropping practices in three selected villages (Abouchiche, Gakem and Ibiaragidi) in Bekwarra Local Government Area, Cross River State, Nigeria. Three villages were purposively selected in Bekwarra Local Government Area, Cross River State, Nigeria, then forty respondents were randomly selected from each village(120 groundnut -based alley farmers were selected). Multiple regression analysis was the main tool of data analysis where different functions were used. The results indicated that Cobb-Douglas production function had the best fit in explaining the relationship between output of groundnut and inputs used, the co-efficient of multiple determinant(R2= 0.60) indicated that sixty per cent of variability in output of groundnut is explained by the independent variables. The F-value of 16.61 indicates that the overall significance of the model at one per cent level, indicating that there is a significant linear relationship between the independent variables taken together and yield of groundnut produced in Bekwarra Local Government Area, Cross River State. The results also indicates that groundnut-base alley cropping system of production by small-scale farmer was profitable but respondents were inefficient in production of groundnut; they over-utilized or under- utilized resources (allocative in-efficiency). However, expectation of large profits had cause most of respondents in study area to shift from traditional bush fallow system of farming to improved groundnut alley-base cropping system that is more profitable. The study recommended that government should provide agro chemicals, improved farm implements, storage facilities and marketing facilities. Beside that, banks should provide loans at low interest rate to both small and large –scales farmers. The unemployed youth are encouraged to go into large scale groundnut based- alley farming business. Finally, government should make and implement policy that will enable farmers to reduce cost of production and maximize profit in short and long term production of groundnut through agro- forestry practices.
Keywords: Alley cropping; Cobb-Douglas; Groundnut; Productivity; Profitability